IMPLEMENTATION OF SITUATIONAL LEADERSHIP STYLE HEAD OF MADRASAH ALIYAH IN IMPROVING TEACHER PERFORMANCE QUALITY (Description Study at MA Assalam Darul Faizah and MA Al-Ma'tuq Sukabumi Regency) - E. Hasanah; Iim Wasliman; Sutaryat Trianmansyah; Husen Saeful Ihsan (IJGIE (International Journal of Graduate of Islamic Education), 2022)
The problem of teacher performance is still visible and shows the quality of performance that has not been maximized. This means that not all teachers carry out their main tasks and functions optimally according to the Standards (Peraturan Menteri Pendidikan Nasional Republik Indonesia Nomor 16 Tahun 2007 Tentang Standar Kualifikasi Akademik Dan Kompetensi Guru, 2007). Academic Qualifications and Teacher Competencies, especially in the mastery of pedagogic competence and professional competence. The teacher still uses very simple teaching preparation, has not fully used the prepared RPP curriculum reference, the dominant teacher uses the lecture method. This study uses a qualitative approach with descriptive methods supported by primary and secondary data types and data collection techniques of observation, interviews and documentation. The general purpose of this study was to determine and analyze the Implementation of the MA Principal Situational Leadership Style in Improving the Quality of Teacher Performance. The results of this study indicate that the Head of MA has implemented a situational leadership style in improving the quality of teacher performance. This is shown in the ability to explain and direct, offer or give instructions, involve, delegate tasks and obligations that are known from the objectives, substance, process, and results